Young people's low back pain and awareness of postural habits: A cross-sectional study - Schwertner D.S.* (2022)
© 2022 - IOS Press. All rights reserved.BACKGROUND: Young people tend to spend most of their time in activities involving inappropriate positions, which can promote musculoskeletal alterations and disorders. OBJECTIVE: To investigate the prevalence of low back pain (LBP) in young people and analyse its associations with daily postural habits. METHODS: Cross-sectional and retrospective study evaluating 679 Brazilian young people (15 to 18 years old), using questionnaires about LBP and awareness of postural habits. The prevalence values were calculated for the present moment, the last three months and throughout life. The Mann-Whitney U test and the Chi-square test were applied. RESULTS: The prevalence of LBP at the present moment was 27.2%, 57.7% over the last three months and 73.9% throughout life. Boys and girls presented significantly different values, a larger number of girls manifesting pain for the three moments. The associated postural habits were: turning the body, reduction of lumbar lordosis when seated, not placing the feet on the floor, crossing the legs when sitting in the classroom and at home, sitting or lying in an inappropriate position, and distributing the body asymmetrically on the legs when standing. CONCLUSIONS: Young people from 15 to 18 years of age show a high prevalence of low back pain. Inadequate postural habits adopted during everyday activities are associated with this complaint. These findings could contribute to the implementation of prevention and rehabilitation strategies.